2017
DOI: 10.1016/j.trci.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting butyrylcholinesterase for preclinical single photon emission computed tomography (SPECT) imaging of Alzheimer's disease

Abstract: IntroductionDiagnosis of Alzheimer's disease (AD) in vivo, by molecular imaging of amyloid or tau, is constrained because similar changes can be found in brains of cognitively normal individuals. Butyrylcholinesterase (BChE), which becomes associated with these structures in AD, could elevate the accuracy of AD diagnosis by focusing on BChE pathology in the cerebral cortex, a region of scant BChE activity in healthy brain.MethodsN-methylpiperidin-4-yl 4-[123I]iodobenzoate, a BChE radiotracer, was injected intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Recent findings indicated that some of NAEs are competitive (anandamide) and non-competitive (oleoylethanolamine and palmitoylethanolamine) inhibitors of plasma butyrylcholinesterase (BuChE) [29]. Changes in the level and activity of this enzyme were indicated in the pathogenesis of diseases associated with cognitive disorders (AD, multiple sclerosis) [30,31].…”
Section: Total Level Of Phospholipids and Level Of Individual Phosphomentioning
confidence: 99%
“…Recent findings indicated that some of NAEs are competitive (anandamide) and non-competitive (oleoylethanolamine and palmitoylethanolamine) inhibitors of plasma butyrylcholinesterase (BuChE) [29]. Changes in the level and activity of this enzyme were indicated in the pathogenesis of diseases associated with cognitive disorders (AD, multiple sclerosis) [30,31].…”
Section: Total Level Of Phospholipids and Level Of Individual Phosphomentioning
confidence: 99%
“…If so, supplementing current clinical signs and symptoms with targeted molecular imaging of olfactory structures, such as the POG, could serve as noninvasive biomarkers of early AD. Preferential involvement of BChE with AD pathology elsewhere suggests that such targeted imaging of BChE in the POG may be particularly sensitive at detecting and distinguishing early AD changes .…”
Section: Discussionmentioning
confidence: 99%
“…However, advanced progression of AD involves a rapid decrease of AChE levels in the brain of9 0 %, which is accompanied in later-stage AD by elevated BChE expression. AChE and BChE exhibit very different localisations, biochemical features, and physiological functions [11]; however, BChE can take over the hydrolytic function of AChE [12][13][14][15][16]. These findings make BChE an attractive target for the development of more potent drugs for combatting AD [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[ 123 I]MP4Bz was applied in single-photon emission computed tomography (SPECT) studies, in which it was possible to distinguish cerebral cortical BChE activity in wild-type mice from an AD model [16]. This represents an important proof of concept, which demonstrates that BChE can indeed serve as a promising biomarker in AD diagnostics [15,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation